The Effect of Whistleblowing and Professional Skepticism on Fraud Detection Audit with Fraud Audit Training as a Moderating Variable - Juliana Waromi; Agustinus Salle; Nelly A. Fonataba (AIBPM Publisher, 2024)
Fraud detection was examined through a survey. Specifically, this research investigated the impact of whistleblowing and professional skepticism on fraud detection by using moderating variable fraud audit training. All of the respondents were auditors working for the Supreme Audit Institution Representative of Papua Province in Indonesia. Using a census sampling method. The data collection technique used an instrument through a questionnaire. A total of 40 auditors participated in this study. The application of moderated regression analysis (MRA) approach for data analysis. This study yields three key findings. Firstly, whistleblowing exerts a notable influence on fraud detection. Secondly, professional skepticism demonstrates a significant impact on fraud detection. Thirdly, the study reveals that fraud audit training does not act as a moderator in the relationship between professional skepticism and fraud detection. The implications of this results for internal and external audits of government enhance professional skepticism through fraud audit training and using whistleblowing information.